2017
DOI: 10.14814/phy2.13391
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fear of falling on vestibular feedback control of balance

Abstract: Vestibular sensation contributes to cervical‐head stabilization and fall prevention. To what extent fear of falling influences the associated vestibular feedback processes is currently undetermined. We used galanic vestibular stimulation (GVS) to induce vestibular reflexes while participants stood at ground level and on a narrow walkway at 3.85 m height to induce fear of falling. Fear was confirmed by questionnaires and elevated skin conductance. Full‐body kinematics was measured to differentiate the whole‐bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This implies that while conscious movement processing can influence perceived instability, this is not the sole mechanism underpinning (distorted) threat-related perceptions of instability. Previous research has reported increased sensory gain (specifically with regards to muscle spindle sensitivity [34,35] and vestibular feedback [35][36][37][38]) when balance is threatened, which may result in anxious or fearful individuals perceiving themselves to be swaying at greater amplitudes than actually exhibited [39]. As self-reported levels of fear remained identical between Threat and Threat-Distraction, it is, therefore, likely that altered perceptions of sway resulting from increased sensory gain will persist-to some degree, at least-even when attention to balance is withdrawn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that while conscious movement processing can influence perceived instability, this is not the sole mechanism underpinning (distorted) threat-related perceptions of instability. Previous research has reported increased sensory gain (specifically with regards to muscle spindle sensitivity [34,35] and vestibular feedback [35][36][37][38]) when balance is threatened, which may result in anxious or fearful individuals perceiving themselves to be swaying at greater amplitudes than actually exhibited [39]. As self-reported levels of fear remained identical between Threat and Threat-Distraction, it is, therefore, likely that altered perceptions of sway resulting from increased sensory gain will persist-to some degree, at least-even when attention to balance is withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that fear and conscious movement processing influence different aspects of sensory processing (and, thus, uniquely contribute to perceptions of stability). For example, research has described how vestibular processing is altered during conscious balance processing (when induced independently from postural threat) in a manner that is seemingly different to that observed in participants fearful of falling [ 38 , 40 ]. While it is difficult to isolate the extent to which conscious movement processing mediates the relationship between increased anxiety/fear and distorted perceptions of unsteadiness, the current work clearly identifies that such cognitive processes can mediate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…While we observed significant vestibular-evoked balance responses in all participants from the low back and ankle sensors, other IMU placements could be explored. Notably, de Melker Worms et al (2017) observed the strongest lower limb vestibular responses from the knee kinematics, suggesting that this may be an ideal placement for measuring vestibular responses. However, we chose the ankles as the location for the IMUs to better identify gait events as well as possibly characterize vestibular-evoked balance responses.…”
Section: Discussionmentioning
confidence: 97%
“…By computing the coherence between a commonly used stochastic EVS signal and the ML linear acceleration from IMUs positioned on the low back and both ankles, we found vestibular-evoked balance responses above a 99% confidence interval in all participants for both the 52 and 78 steps/min cadence conditions. This technique has previously been used to compare an applied vestibular error-signal with muscle activity, ground reaction forces and moments, or body kinematics in quiet standing ( Dakin et al, 2007 ; Horslen et al, 2014 ; de Melker Worms et al, 2017 ) and walking conditions ( Bent et al, 2004 ; Iles et al, 2007 ; Blouin et al, 2011 ; Dietrich et al, 2020 ). Here, we extended these findings by demonstrating that it is possible to use linear accelerations measured from wearable IMUs to characterize vestibular-evoked responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation